2017
DOI: 10.1111/jch.13025
|View full text |Cite
|
Sign up to set email alerts
|

Interannual study of spot urine–evaluated sodium excretion in young Japanese women

Abstract: The authors investigated interannual differences in the sodium excretion levels of young healthy Japanese women as estimated from spot urine analysis at Nakamura Gakuen University from 1995 to 2015. Participants included 4931 women aged 18 to 20 years who were classified into three time periods according to year of health check:first (1995-2001), second (2002-2007), and third (2008-2015). Estimated daily urinary sodium and potassium excretion levels and the sodium to potassium ratio were 120.6±31.9 mmol, 35.2±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Japan is among the countries with the highest salt intake in the world, and since this dietary behavior is formed since adolescence, it is necessary to establish salt management and a practical salt‐reduction education tool for young individuals. The present study was the first to report that frequent self‐monitoring using a self‐monitoring salt excretion level measurement device can improve 24‐hour urinary sodium/potassium ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Japan is among the countries with the highest salt intake in the world, and since this dietary behavior is formed since adolescence, it is necessary to establish salt management and a practical salt‐reduction education tool for young individuals. The present study was the first to report that frequent self‐monitoring using a self‐monitoring salt excretion level measurement device can improve 24‐hour urinary sodium/potassium ratio.…”
Section: Discussionmentioning
confidence: 99%
“…According to a national study on daily salt intake among 1043 Japanese women aged 18‐22 years, the mean values of salt intake based on 24‐hour urine collection and a dietary questionnaire were 9.8 g and 9.2 g, respectively, which substantially exceeded the Japanese target salt‐intake value of 7.0 g . We also reported that the mean estimated daily salt‐intake value for female university students (mean age of 17.9 years) who entered university from 1995 to 2015 was 8.1 g, and that only 31.3% of the students consumed more salt than the Japanese target value of 7.0 g . A study estimating the decrease in the mortality rate by reducing salt intake showed that the earlier the age at which salt restriction was started, the more effective it was in decreasing the mortality rate .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The most important message of the study by Yasutake and colleagues is that Japanese women attending the Department of Nutritional Sciences at Nakamura‐Gakuen University have reduced their sodium intake during the past 20 years. It was noted, however, that these women were likely more motivated, as they were a faculty involved in nutrition, and that women in other faculties might be less interested in health and therefore consumed more salt.…”
Section: Salt Intake: Japanese Studiesmentioning
confidence: 99%
“…Yasutake and colleagues have published an interesting study on the interannual changes in the sodium excretion levels, as estimated from spot urine, of young healthy Japanese women. The authors have reported a significant reduction in urinary sodium excretion during the past 20 years, independent of body weight and consistent with a gradual decline in sodium intake.…”
Section: Introductionmentioning
confidence: 99%